Lemierre's Syndrome Due to the Zoonotic Anaerobe Bacteroides pyogenes: Case Report and Literature Review. (26th May 2021) - Goggin, Kathryn P; Beckmann, Nicholas; Bettin, Kristen; Carrillo-Marquez, Maria; Wood, Joshua; Arnold, Sandra R
Abstract: Although Fusobacterium necrophorum is well described as an emerging pathogen of acute mastoiditis in young children, infection with other anaerobes can lead to similar severe sequelae including intracranial and extracranial suppurative thrombophlebitis and sepsis. We describe a patient whose unremarkable exposure history assumed increased significance upon obtaining the results of 16S next generation sequencing from a surgical specimen. The novel pathogen Bacteroides pyogenes is reviewed herein.